Look before you LIEEP: Practicalities of using ecological systems social marketing to improve thermal comfort. Issue 1 (2nd January 2018) - Gordon, Ross; Butler, Katherine; Cooper, Paul; Waitt, Gordon; Magee, Christopher
Abstract : Purpose: This paper aims to present a discursive and evaluative analysis of Energy + Illawarra, an Australian Government Low Income Energy Efficiency Program (LIEEP) funded interdisciplinary social marketing energy efficiency programme. Energy + Illawarra was a community programme working with low-income older people in Australia and involving social marketers, human geographers and engineers. The paper aims to identify how ecological systems theory can inform social marketing, and what practicalities there may be in doing so. The paper also aims to assess whether a social marketing programme that draws on ecological systems theory can have a positive impact on people's thermal comfort. Design/methodology/approach: First, the paper uses critical discursive analysis to examine the use of various elements of a social marketing energy efficiency programme in relation to the different levels of ecological systems theory. Second, a longitudinal cohort survey study design is used to evaluate the programme's influence on people's perceptions of thermal comfort and satisfaction with thermal comfort in their homes. Findings: The study found that ecological systems theory could be an effective framework for social marketing programmes. The evaluation study found that the intervention had a positive impact on participant's perceptions of thermal comfort, satisfaction with thermal comfort and attitudes towards energy efficiency. However, the paper identifies some potential tensions in using ecological systems theory and suggests that issues of power, representation, agenda setting, the need for reflexive practice and consideration of unintended consequences are important considerations in social marketing programmes. Originality/value: The work presented here suggests that multi-level social marketing programmes that draw on ecological systems theory can make a useful contribution to social change as demonstrated by the evaluation survey finding positive impacts on thermal comfort and attitudes of participants. However, issues of power, representation, agenda setting, the need for reflexive practice and consideration of unintended consequences should be considered in social marketing programmes.